Manegment of the medical waste in the kindy hospital - فيض الله, جواد عبد الواحد (Journal of Economics and Administrative Sciences, 2018)
The problem of medical waste over the past tow decades has emerged as one of the most important issues.Which have negative effects on health and the environment ,and as a result specialists looked into the field.Public health and research issues . This phenomenon in all its dimensions and efforts made For their containment through the development of health and environmental controls for the disposal of such wastes.In a safe manner starting form the source of these wastes and the various health organizations are  finished The final treatment ,and this is why the producers of hazardous medical waste.                                                                                       To reduce the production rates of these wastes in quantity and quality by developing the equipment The equipment delivered ,the wide range of clean technology and the selection of alternatives and lower raw materials.